Determinants of Profitability with Capital Structure as Moderator in Consumer Non-Cyclicals (2022–2024) - Puspita, Dita Candra; Tiswiyanti, Wiwik; Jumaili, Salman; Mukti, Mukti (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: Profitability is an important indicator in evaluating a company’s financial performance, particularly in generating profits and returns for investors. Background Problems: Profitability is a key measure of financial performance; however, the consumer non-cyclicals sector has experienced a decline in profitability in recent years. This condition reflects inefficiencies in managing company resources. Internal factors such as liquidity, solvency, and activity are considered to influence profitability, although previous studies have shown inconsistent results. Novelty: This study incorporates capital structure as a moderating variable in the relationship between liquidity, solvency, and activity on profitability in consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Research Methods: This study employs a quantitative approach using secondary data obtained from 116 companies (348 observations). Data analysis is conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Finding/Results: The results indicate that solvency has a significant negative effect and activity has a significant positive effect on profitability, while liquidity and capital structure have no significant effect. Furthermore, capital structure is unable to moderate the relationship between these variables and profitability. Conclusion: Overall, activity has the greatest influence on profitability compared to other variables, indicating that companies need to improve the effectiveness of asset management to enhance financial performance sustainably.